2021
DOI: 10.1016/j.dcn.2021.100915
|View full text |Cite
|
Sign up to set email alerts
|

The origins and development of speech envelope tracking during the first months of life

Abstract: Highlights The adult brain tracks the modulation of the amplitude of speech, i.e. its envelope. We tested if preverbal infants, i.e. newborns & 6-month-olds, track the speech envelope. Infants track the envelope phase at both ages in the native language & in unfamiliar languages. Infants track the envelope amplitude in the native language at birth but not at 6 months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(91 citation statements)
references
References 54 publications
(75 reference statements)
7
84
0
Order By: Relevance
“…There are three previous infant language-based cortical tracking studies of speech, two with 7 month-old infants (39, 40) and one with neonates and 6-month-olds (41). These prior studies were not longitudinal and adopted either a forward linear modelling approach (detailed methods; 37), or a cross-correlation analysis, to estimate how well the amplitude envelope of IDS was represented in the cortical activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three previous infant language-based cortical tracking studies of speech, two with 7 month-old infants (39, 40) and one with neonates and 6-month-olds (41). These prior studies were not longitudinal and adopted either a forward linear modelling approach (detailed methods; 37), or a cross-correlation analysis, to estimate how well the amplitude envelope of IDS was represented in the cortical activity.…”
Section: Introductionmentioning
confidence: 99%
“…A backward ‘stimulus reconstruction’ version of the TRF linear modelling technique, not yet used with infants, was employed here. The backward mTRF uses information from all EEG channels simultaneously to reconstruct the speech envelope, thereby enabling increased sensitivity to signal differences between highly correlated response channels, thus offering several advantages (47) over forward modeling (39, 40) or cross-correlation approaches (41). The mTRF provides a single summary measure of speech-EEG coupling for data recorded over long periods of time by assessing the fidelity of the reconstruction (47).…”
Section: Introductionmentioning
confidence: 99%
“…The neural ability to discriminate these auditory cues revealed here highlights the readiness of the infant brain to process speech rhythm (Mehler et al, 1988). RISE TIME DETECTION IN INFANCY Mechanistically, rise time processing enables the infant brain to represent the amplitude envelope of the highly rhythmic stimulus that is infant-directed speech (Attaheri et al, 2021, preprint;Leong et al, 2017;Ortiz Barajas, Guevara & Gervain, 2021). Accordingly, neural rise time discrimination supports the infant brain in the acquisition of language.…”
Section: Discussionmentioning
confidence: 63%
“…Neural tracking of auditory information is already known to occur in infants as well as adults (Jessen et al, 2019). Ortiz Barajas, Guevara & Gervain (2021) found evidence for neural tracking of the speech envelope even among newborn infants. Kalashnikova, Peter and colleagues (2018) found that the envelope of infant-directed speech (filtered to 1 to 8 Hz) is represented in the brain of seven-month-old infants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation